Community, health and rehabilitation - Giustini, Alessandro (Journal of Community Medicine and Health Solutions, 2023)
The problems of guaranteeing the best possible social and health services in every part of the world to combat any form of disability and limitation of participation for all, as indicated by international ethical-political documents, are still very great. A critical point that could favour this progress is to enhance the integration between the growing potential of rehabilitation science (medical and clinical evidence, technologies, and training of numerous operators..) and the ability of communities as a whole to stimulate, support and qualify these interventions with the participation of citizens (families, neighbours and associations) who can voluntarily actively carry out important synergistic actions in many fields. This could develop in any socio-economic condition; in developed ones supporting and finalizing any treatment in common life and in developing countries offering competencies and knowledge to the strong funding actions of community projects aimed at populations with disabilities in this part of the World. The community of rehabilitation professionals, national governments and rulers, and international institutions (UN, WHO..) must well understand this aspect and make it their own in training, in the definition of care protocols, in the definition of the organization of socio-health and rehabilitation systems in each country in relation to the different local economic and cultural conditions.